Impact of Tau on Neurovascular Pathology in Alzheimer's Disease - Canepa, Elisa; Fossati, Silvia (Frontiers in Neurology, 2021)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder and the most prevalent cause of dementia. The main cerebral histological hallmarks are represented by parenchymal insoluble deposits of amyloid beta (Aβ plaques) and neurofibrillary tangles (NFT), intracellular filamentous inclusions of tau, a microtubule-associated protein. It is well established that cerebrovascular dysfunction is an early feature of AD pathology, but the detrimental mechanisms leading to blood vessel impairment and the associated neurovascular deregulation are not fully understood. In 90% of AD cases, Aβ deposition around the brain vasculature, known as cerebral amyloid angiopathy (CAA), alters blood brain barrier (BBB) essential functions. While the effects of vascular Aβ accumulation are better documented, the scientific community has only recently started to consider the impact of tau on neurovascular unit pathology in AD. Emerging compelling evidence points to transmission of neuronal tau to different brain cells, including astrocytes, as well as to the release of tau into brain interstitial fluids, which may lead to perivascular neurofibrillar tau accumulation and toxicity, affecting vessel architecture, cerebral blood flow and vascular permeability. BBB integrity and functionality may therefore be impacted by pathological tau, consequentially accelerating the progression of the disease. Tau aggregates have also been shown to induce mitochondrial damage: it is known that tau impairs mitochondrial localization, distribution and dynamics, alters ATP and reactive oxygen species production, and compromises oxidative phosphorylation systems. In light of this previous knowledge, we postulate that tau can initiate neurovascular pathology in AD through mitochondrial dysregulation. In this review, we will explore the literature investigating tau pathology contribution to the malfunction of the brain vasculature and neurovascular unit, and its association with mitochondrial alterations and caspase activation, in cellular, animal, and human studies of AD and tauopathies.